2015
DOI: 10.3389/fnhum.2015.00671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paired-Pulse Electrical Stimulation on the Activity of Cortical Circuits

Abstract: Objective: We investigated the transient effect of short-duration paired-pulse electrical stimulation (ppES) on corticospinal excitability and the after-effect of long-duration ppES on excitability, short-latency afferent inhibition (SAI), and afferent facilitation (AF).Methods: A total of 28 healthy subjects participated in two different experiments. In Experiment 1, motor-evoked potentials (MEPs) were measured in the abductor pollicis brevis (APB) and abductor digiti minimi (ADM) muscles before and immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…One possible explanation for PES-induced MEP facilitation is the specific timing of direct Ia fiber activation by PES and somatosensory input from contracting muscles. Saito et al (2015) reported MEP potentiation and cortical inhibitory circuit depression following 10 Hz paired-pulse electrical stimulation with 5-ms inter-pulse intervals to the median nerve (mixed nerve) even when stimulus intensity was 80% of MT (i.e., without muscle contraction). Therefore, in the mixed nerve stimulation with muscle contraction condition, M1 excitability may increase if somatosensory inputs from Ia fibers induced by direct electrical stimulation and somatosensory inputs from muscle contraction arrive with a time difference of ~5 ms. On the other hand, Chipchase et al (2011a) showed that the MNS with intensity of muscle twitch at a frequency of 10 Hz did not change, although muscle contraction occurred.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for PES-induced MEP facilitation is the specific timing of direct Ia fiber activation by PES and somatosensory input from contracting muscles. Saito et al (2015) reported MEP potentiation and cortical inhibitory circuit depression following 10 Hz paired-pulse electrical stimulation with 5-ms inter-pulse intervals to the median nerve (mixed nerve) even when stimulus intensity was 80% of MT (i.e., without muscle contraction). Therefore, in the mixed nerve stimulation with muscle contraction condition, M1 excitability may increase if somatosensory inputs from Ia fibers induced by direct electrical stimulation and somatosensory inputs from muscle contraction arrive with a time difference of ~5 ms. On the other hand, Chipchase et al (2011a) showed that the MNS with intensity of muscle twitch at a frequency of 10 Hz did not change, although muscle contraction occurred.…”
Section: Discussionmentioning
confidence: 99%
“…While other iEEG studies have examined TBS-induced oscillatory changes, notably increasing theta band power 12,100 , the voltage effects of TBS and the dynamics of these neural responses within and across stimulation trains remain unexplored. This is critical as these features voltage changes after stimulationunderlie neuroplasticity studies in animal models [57][58][59][60] . Our results indicate the reliable quantification and temporal tracking of evoked response immediately following each high-frequency burst (TBS response).…”
Section: Discussionmentioning
confidence: 99%
“…McKay et al (2002) measured changes in MEPs at 15 min intervals for up to 2 h of neuroelectrical stimulation in healthy participants, reporting that the MEP peaked 45−60 min after the first stimulus [24]. Saito et al also reported that there was no change in the MEP amplitude values before and after 20 min of paired-pulse electrical stimulation [25]. As the results of the present study are similar to those of previous ones, we believe that 20 min of PES stimulation is insufficient time when MEP is evaluated using the FDI muscle as the guiding muscle, and that stimulation for >40 min may increase the excitability of the primary motor cortex.…”
Section: Discussionmentioning
confidence: 99%